FAKTOR DETERMINAN HANDOVER DALAM KESELAMATAN PASIEN - Nirwan Nirwan; Said Devi Elvin (Poltekkes Kemenkes Aceh, 2023)
Currently patient safety continues to be a major concern for nurses. One of the activities that can have an impact on patient safety is handovers carried out by nurses. Data shows that medical and treatment errors can threaten patient safety, 70% of them because of non-optimal handover activities by nurses. However, there are several organizational factors that influence the success of handover activities by nurses. This research is a quantitative study with a correlational design. The population was all nurses in the inpatient room of the Hospital in Banda Aceh, with a total of 175 nurses. The instrument for measuring organizational factors was adopted from the Hospital Survey on Patient Safety from the U.S. Agency for Healthcare Research and Quality (AHRQ), Department of Health and Human Services. Then, the instrument developed by Arianti was used for measuring nurse handover. Data were analyzed by using Chi-Square test and binary logistic regression with stepwise method. The results showed that of the 3 organizational factor variables in patient safety, 2 variables namely enabling factor (P-value: 0.000) and enacting factor (P-value: 0.002) were significant predictors of nurse handover in the inpatient ward. Furthermore, the data analysis indicated enabling factor is the most dominant predictor of nurse handover, with an odds ratio (OR) of 116.999. Meanwhile, the elaborating factor did not significantly affect the handover of nurses in the inpatient ward. Organizational factors that influence the success of the handover of the nurse in the inpatient unit are enabling and enacting factors.